Efficient bioleaching of high-magnesium low-grade copper-nickel sulfide ore: optimization and mechanisms - Duo-Rui Zhang; Dai-Ying Wei; Jing Zhang; Hong-Rui Chen; Zi-Jie Jin; Lei Zheng (Minerals Engineering, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Synergistic dual-site passivation via ionic liquid engineering for efficient and stable deep-red CsPbI₃ QLEDs - Xiaoke Li; Jinjian Lu; Rui Han; Xiaoqing Jing; Yuyu Zhang; Jintao Wang; Ren Sheng; Ping Chen (Chemical Engineering Journal, 2026)

3D Co, N co-doped carbon dots/TiO2 heterostructures: Unlocking radical-nonradical dual-pathway synergy in efficient PMS photo-activation - Pengze Wang; Jing Liang; Zhijun Li; Yang Qu; Pengkai Shen; Ziyu Chen; Junkang Lin; Rui Yan; Jing Wu; Liqiang Jing (Journal of Environmental Chemical Engineering, 2026)

Synergistic effect of alkaline and heat treatment in inhibiting syneresis of CaSO₄-induced cold-set peanut protein isolate gel: Insights into structural modifications and gelation kinetics - Jing Chen; Rui Li; Zining Fan; Yu Wang; Yuntao Wang; Yanhong Bai (Food Chemistry, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Efficient directional conversion of chemical energy contained in organic matter into cellular biomass energy induced by different terminal electron acceptors during activated sludge process - Rui Liu; Wen-Jing Li; Shao-Yang Liu; Jin-Song Guo; Fang Fang; You-Peng Chen; Peng Yan (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

A robust method for the simultaneous quantification of 30 legacy and emerging per- and polyfluoroalkyl substances (PFAS) across multiple marine media - Nuo Chen; Jing-Chun Feng; Li Tang; Rui Hou; Si Zhang (Marine Pollution Bulletin, 2026)

Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

PbrSLAH3b mediates nitrate-dependent regulation of pollen tube growth in pear - Guodong Chen; Peng Cao; Jia Gao; Weitao Xiao; Cong Jing; Rui Cheng; Huijun Jiao; Jizhong Wang; Juyou Wu (Plant Science, 2026)

Climate risk assessment of rubber tree powdery mildew in China - Rui Bai; Jing Wang; Ning Li; Renwei Chen (European Journal of Agronomy, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Bioinspired core-shell structured electrospun fibers guide neural stem/progenitor cell lineage development for spinal cord injury repair - Jiaxin Chen; Zilong Rao; Rui Cui; Rongli Deng; Jing Zhou; Daping Quan; Xipeng Guan; Houqing Long; Ying Bai (Chemical Engineering Journal, 2026)

Role of immune dysregulation in aristolochic acid–induced multisystem toxicities: an insight from systems toxicology - Jing Yang; Xiaodan Lai; Hongwei Luo; Yue Luo; Bin Chen; Jing Lei; Yuanqiang Wang; Yuanlin Ma; Rui Xiong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Long term salinity acclimation buffers combined impacts of heat–salinity on Daphnia by reconfiguring osmoregulatory transcription - Jing Huang; Yalin Chen; Zihao Jin; Rui Wu; Zhou Yang (Marine Environmental Research, 2026)

Evolution of deep carbonate reservoir parameters under hydro-mechanical coupling - Jing Li; Da Chen; Zhengyang Li; Yuhang Dai; Wenbo Guo; Rui Zheng (Journal of Applied Geophysics, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

Bioinspired superamphiphobic microreactor for efficient fabrication of cellulose nanocrystal photonic pigments - Kai Xiong; Jing Guo; Yingying Chen; Rui Tong; Yunjia Cai; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Quantifying land-use-specific non-point source pollution in a forest-dominated watershed using control-section mass balance and ridge regression - Zhang Jing; Zhao Rui-rui; Yang Lu Ping; Chen Zi Jing; Xing Bing; Peng Shi-tao (Process Safety and Environmental Protection, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Rhizosphere microbiome and soil health effects on ginseng growth performance and ginsenoside accumulation - Jing Fang; Rui Liu; Kemeng Zhang; Yingmei Sun; Yan Xue; Changbao Chen; Tao Zhang; Qinghe Zhang; Jia Chen (Plant and Soil, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Duplex real-time qPCR assay targeting β-tubulin SNPs for detection of albendazole resistance in Haemonchus contortus - Xindi Chen; Lili Zhang; Tengyu Wang; Hao Zhang; Rui Wang; Jing Lu; Wa Gao; Wenlong Wang; Chunxia Liu (The Veterinary Journal, 2026)

Glucose stabilizes the KLF5 transcription factor to promote glycolysis and malignancy of basal-like breast cancer - Rui Liu; Yu Tang; Wenjing Liu; Chunli Zhou; Zhongmei Zhou; Wen Liu; Qiang Yu; Longlong Zhang; Jian Sun; Jing Peng; Yongchun Zhou; Dewei Jiang; et al. (Science Bulletin, 2026)

Techno-economic assessment of offshore wind multi-path energy conversion and storage-transport: electricity, hydrogen, and methanol - Lei Pan; Yunfei Ding; Yuxuan Wang; Yi Pang; Jianwei Chen; Yanwei Jing; Haibo Qiu; Rui Gao; Liyang Zhang (Ocean Engineering, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

A sucrose–jasmonic acid feedback loop drives stem cell senescence in Arabidopsis - Yan-die Chen; Rui Zhang; Jing Yang; Zhong Zhao (Molecular Plant, 2026)

Ascosphaera apis-derived microRNA-like RNAs mediate cross-kingdom regulation of gene expression in western honeybee larvae - Xiaoxue Fan; Nian Fan; Tao Wu; Jing Kang; Jiarun Yang; Jing Tian; Xihan Luo; Dafu Chen; Jianfeng Qiu; Rui Guo (Journal of Invertebrate Pathology, 2026)

Ascosphaera apis invasion alters the expression pattern, alternative splicing and alternative polyadenylation of transcripts in the eastern honeybee larval gut - Jianfeng Qiu; Fangji Wang; Xiang Li; Tao Wu; Xin Jing; Zhenzhen Zuo; Jing Tian; Dafu Chen; Rui Guo (Journal of Invertebrate Pathology, 2026)

Manganese oxide reduction by non-extracellular respiratory bacteria and fraxetin from plant residues decomposition - Wei Chen; Rui Bai; Xudong Zhou; Biyi Zhao; Chongyuan Ren; Junpeng Li; Liping Dai; Yacen Fang; Jing Zhang; Andreas Kappler; Feng Zhao; Yong Xiao (Journal of Environmental Sciences, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Integrative analysis of physiology, transcriptomics, and metabolomics unveils mechanisms in soybean (Glycine max (Linn.) Merr) response to alkaline stress - Qian Li; Bo Chen; Ziyu Yang; ChenJing Li; Qing Jing; Qinghong Lu; Rui Ni; Pengzhi Mao; Li Zhang; Xinyong Guo (Plant Science, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Assessing spring frost-induced production losses across China’s apple planting regions - Renwei Chen; Jing Wang; Yang Li; Rui Bai; Zhihong Gong; Zhenjiang Qu; Zhangyan Le; Jianshuo Zhou (International Journal of Biometeorology, 2026)

Energy input rate as a key switch: tuning product distribution and carbon structure in waste tire pyrolysis via conventional and microwave heating - Peng Liu; Shuxiao Wang; Jing Gu; Rui Shan; Yanzhi Sun; Junqing Pan; Haoran Yuan; Yong Chen (Fuel, 2026)

The mechanism of reducing the oil content of fried instant noodles by adding sugar alcohol: microstructure, surface properties and molecular structure - Rui He; Xiaomeng Ma; Ju Chen; Chengrong Zheng; Dingwu Zhang; Chong Liu; Jing Hong; Binghua Sun; Mei Liu; Jiaying Shang; Zipeng Liu; Xueling Zheng (Food Research International, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Development and initial validation of spicy food somatosensory experience scale - Huizhen Qiu; Yidan Rui; Jiaqi Jing; Yuan Gao; Jiangming Chen; Yuchen Zhang; Siwen Zhen; Xiao Gao (Food Quality and Preference, 2026)

Rapid-gelating starch from potential ginger processing waste: Multi-scale structural analysis enabling high-precision 3D printing for health-focused food applications - Rui He; Shanshan Li; Jing Wang; Zhu Zhu; Wenhao Luo; Kun Pan; Fengwei Xie; Ying Chen; Tao Yang (Food Hydrocolloids, 2026)

Construction and application of controlled-release preservation pads based on Zein/sodium caseinate-stabilized oregano essential oil Pickering emulsions - Liu Yang; Wenwen Chen; Xinyu Zhang; Rui Xiao; Xue Ding; Zhipeng Jing; Hongyuan Zhang (Food Hydrocolloids, 2026)

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Diagnostic Value of Fast Stroke Imaging for Salvageable Brain Tissue and Collateral Circulation in Stroke Patients - Dongxue Wang; Shuang Liang; Zhongzhen Yue; Ye Tian; Jing Zhang; Liyu Qiao; Rui Li; Junqiang Xu; Rui Chen; Fanxiang Meng; Yichao Wang (Journal of Medical and Biological Engineering, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Correction to: Assessing the distribution pattern of Saussurea medusa under climate change using an optimized MaxEnt model in Qinghai‑Xizang Plateau - Jing‑Hua Chen; Rui‑Tao Yu (Environmental Monitoring and Assessment, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Nitrogen form drives divergent plant N:P stoichiometric responses in karst grasslands - Jing Zhou; Yutao Li; Xinyue Yang; Zhou Li; Rui Dong; Chao Chen; Jihui Chen (Plant and Soil, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Regional Heatwave Characteristics and Future Projections in China Using NEX ‐ GDDP ‐ CMIP6 Downscaled Data - Rui Zhao; Xilin Xie; Yanling Chen; Hong Wang; Jing Li (International Journal of Climatology, 2025)
Climate change has increased heatwave frequency, duration, and intensity globally, which is expected to worsen under warmer conditions. Understanding heatwave variabilities is crucial for the ecosystem and human health they impact, yet comprehensive assessments over China at different spatiotemporal scales remain limited. This study evaluates 12 NASA Earth Exchange Global Daily Downscaled Projections' CMIP6 (NEX‐GDDP‐CMIP6) downscaled data in simulating historical heatwaves (1981–2010) and their projections under SSP2‐4.5 and SSP5‐8.5 scenarios for near‐term (2031–2060) and late‐term (2071–2100) periods, using CN05.1 observations and key heatwave metrics. The NEX‐GDDP‐CMIP6 ensemble mean (MME) outperforms individual models in simulating heatwave frequency (HWF) and duration (HWD), with 65%–87% of China showing biases within ±10%. While the MME effectively captures HWF trend patterns across China, it fails to simulate decreasing HWD trends over southern China and intensity metrics trends over the Tibetan Plateau. Among the individual models, CMCC‐ESM2, GFDL‐ESM4, and GFDL‐CM4 emerge as the three best‐performing models. Under SSP5‐8.5, about 87% (74%) of regions will experience increases in HWF (HWD). Notably, heatwave frequency over China will exceed 15 events annually during 2071–2100. The entire country will experience intensification of heatwave intensity with larger increments in high‐latitude regions. Furthermore, the likelihood of extreme heatwave events under SSP5‐8.5 is projected to be double under SSP2‐4.5. Northern China faces the highest risk of extreme heatwaves with over 50% probability under late‐term SSP5‐8.5, followed by Southeastern China. Our results offer comprehensive insights into NEX‐GDDP‐CMIP6 simulated heatwave variations, necessary for refining global climate models and understanding future risks.

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Combined inhibition of WEE1 by AZD1775 synergistically enhances CX-5461 mediated DNA damage and induces cytotoxicity in glioblastoma - Meng Cheng; Rui Wang; Ying Pang; Xu Chen; Jing Zhang; Chunlong Zhong (Tissue and Cell, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Effect of combined treatment of pH-shifting and mild heating on gel properties of transglutaminase induced cold-set peanut protein isolate gel - Jing Chen; Si Qiu; Rui Li; Zining Fan; Yu Wang; Yuntao Wang (Food Research International, 2025)

Energy-based insights into multi-stage crushing mechanisms of rock materials: Experimental and numerical study - Qihang Hu; Jing Chen; Chang Li; Rui Gao (Engineering Geology, 2025)

Imidazolium-functionalized hyper-crosslinked polymer for the removal of 99TcO4− from alkaline radioactive wastewater - Mengjie Jing; Zhe Wang; Yujie Miao; Yingsi Huo; Rui Zhang; Geng Chen; Keliang Shi; Kang Kang; Xiaolin Hou (Chemical Engineering Journal, 2025)

pH/ROS responsive hydrogel loaded with bimetallic phenolic nanoparticles: A multifaceted therapeutic strategy for accelerating diabetic wound repair - Jing Zhou; Rui Shi; Chuankai Zhang; Yongcen Chen; Xuemin Ma; Yajuan Hu; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Populus euphratica PeMAX2 counteracts PeGRP2 to stabilize target mRNAs relating to salt tolerance - Jing Li; Jun Yao; Siyuan Ma; Jian Liu; Ziyan Zhao; Zhe Liu; Kexin Yin; Caixia Yan; Kaiyue Dong; Rui Shi; Nan Zhao; Rui Zhao; et al. (Plant Science, 2025)

Millimeter-scale interactions of nitrogen and potassium on denitrification, anammox, and Feammox in soil fertilization zones - Jingjing Lyu; Rui Tian; Runhua Zhang; Peng Chen; Xinxin Jing; Runqin Zhang; Kang Zhao; Yi Liu; Chenhao Lyu; Zhiguo Li (Journal of Environmental Sciences, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Interfacial engineering of 0D/3D CeO2/BA nanoarchitectures for highly efficient and selective CO2 photo-reduction to CH4 based on full-spectrum solar-energy utilization - Rui Xu; Chonghai Deng; Chengchen Wang; Yibin Zhu; Yonghui Tong; Zheng Chen; Peipei Sun; LiLi Wang; Lei Yang; Xin Liang; Yiping Wu; Jing Huang; et al. (Chemical Engineering Journal, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Characterizing apple production in China’s apple planting region: Biophysical simulation and machine learning analysis of quality determinants - Renwei Chen; Jing Wang; Chao You; Rui Bai; Puyu Feng; Yang Li; Gang Zhao; Zhenjiang Qu; Qiuyue Li (European Journal of Agronomy, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Bipartite trophic levels cannot resist the interference of microplastics: A case study of submerged macrophytes and snail - Jun Chen; Zhiqiang Zhang; Nan Shen; Hongwei Yu; Guo Yu; Jing Qi; Rui Liu; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2025)

Investigation into the antagonistic effects and mechanisms of VOCs produced by Saccharomycopsis fibuligera KN-1 against Alternaria alternata - Ruixue Chen; Rui Sun; Jing Liang; Lei Sun; Mingguan Yang; Yongjian Qin (Food Bioscience, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Soil myxomycete community in temperate cropland and influence of straw turnover - Feng-Yun Zhao; Guan-Xiu Guan; Rui-Xuan Xiang; Bai-You Chen; Jing Feng; Jian Liu (Applied Soil Ecology, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Comparative study on the effect of H2O/air/CO2 on the gasification results of wheat straw - Shuxiao Wang; Dexin Kong; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Biomass and Bioenergy, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Development of novel caffeic acid derivatives as multifunctional agents for the treatment of AD - Kerong Hu; Jing Yang; Qiyao Zhang; Xinxin Wang; Yujie Xu; Yuxin Zhang; Zhenghuai Tan; Wenmin Liu; Rui Chen; Zhipei Sang (Medicinal Chemistry Research, 2025)

AdvUNet3+: Segmentation of city-scale heterogeneous building façade materials from street view images - Jing Kai Daniel Tan; Rui Zhu; Jie Song; Zheng Qin; Yanqing Xu; Yumin Chen (Sustainable Cities and Society, 2025)

Exposure routes induce differential intestinal damage in zebrafish from polystyrene microplastics - Zhenhua Yan; Yuqiong Yang; Jing Xiang; Yufang Chen; Peiyuan Zhu; Saiyu Yuan; Rui Huang; Xiaodong Hu; Yiming Ma (Process Safety and Environmental Protection, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Radiochromic perovskite La2MgZrO6:Pr for X-ray imaging and ionizing radiation detection - Zi-Hao Chen; Qiang Tang; Jian-An Zeng; Haijiao Xie; Rui Zou; Jing Wang; Bo-Mei Liu (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Research advances in branched-chain amino acid metabolism in tumors - Zheng Li; Sainan Chen; Xuechao Wu; Fei Liu; Jing Zhu; Jiayi Chen; Xiaojie Lu; Rui Chi (Molecular and Cellular Biochemistry, 2025)

Mechanism insight into sulfidated nano zero-valent iron/biochar activated persulfate for highly efficient degradation of p-chloroaniline - Jingchun Yan; Zihan Guo; Yuyuan Sun; Zichen Yan; Rui Liu; Yudong Chen; Jing Song (Chemosphere, 2025)

Regulation pattern of carotenoid biosynthesis induced by low light stress in Dunaliella - Hao-Hong Chen; Jing-Xuan Wu; Rui-qi Chen; Sacha Fouquay O’Donnell; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Development of a Mitochondrial Marker for Distinguishing Between Ulva linza and Ulva prolifera - Rui Zhai; Chengnuo Tang; Shuying Wang; Jing Ma; Xinshu Li; Guoqiang Chen; Juntian Xu (Journal of Marine Science and Engineering, 2025)
The green tide is the biggest ecological disaster in Yellow Sea in recent decades, and the species composition has varied from year to year. The ITS (internal transcribed spacer) sequence combined with 5S rDNA spacer are the mainstream molecular markers for green macroalgae. The former can perfectly distinguish the majority of Ulva spp. except the LPP (Ulva linza–procera–prolifera) complex, and the latter is used to distinguish U. linza and U. prolifera exactly based on the former. However, in practice, 5S rDNA spacer is difficult to amplify perfectly with universal primers, and this ultimately affects the experimental process. For this reason, we developed a stable mitochondrial marker for the distinction between U. linza and U. prolifera. The phylogenetic tree based on the mitochondrial rps2 (ribosomal protein S2) gene fragment can distinguish the LPP complex into two clades: U. linza and U. prolifera. Therefore, we concluded that the mitochondrial marker can be a great substitute for 5S primers to distinguish U. linza and U. prolifera.

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

Combined uranium-series and trace elements analysis in cold seep bivalves: possibility in hundred-year-scale reconstruction of deep-sea temperature and acidification - Chaofeng Cai; Jing-Chun Feng; Guozhong Wu; Rui Hou; Xiao Chen; Jinyi Liu; Xiaochun Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Despite the pivotal role of deep-sea in the global climate system, effective technology is still limited for reconstructing the key parameters of deep-sea environment such as temperature and acidification, especially at the hundred-year scale. In this study, we assessed the robustness and reliability of using bivalve shells in reconstructing cold seep environments. A significant heterogeneous distribution of trace elements was observed in the shells of clams and mussels from Formosa and Haima cold seeps even if they were collected from the same site, which was caused mainly by the environmental variables rather than physiological characters. The results of the principal component analysis revealed different trace elements ratios in the shell were associated with seepage. In particular, Sr/Ca was identified as a reliable proxy for temperature reconstruction, which performed better than oxygen isotopes. Na/Ca and U/Ca are potential proxies for cold seep acidification, but further validation is needed before their practical application. The age bias using the U-series dating method resulted from high 232 Th and low initial 230 Th/ 232 Th rather than from alpha-recoil processes. The median ages assigned to mussels from the F and Haima cold seeps were 229.5 and 323.5 years, respectively. The lifespan of clams from the Haima cold seep was too short to date accurately. We proposed to conduct feasibility verification and error correction to enhance the method performance in reconstructing the hundred-year evolution of cold seep environment in the South China Sea.

Effect of rhizosphere soil microenvironment interaction on ginsenoside content in Panax ginseng: A case study of three-year-old agricultural ginseng - Zhefeng Xu; Yuqiu Chen; Rui Liu; Yibing Wang; Chunshuo Liu; Jing Fang; Qinghe Zhang; Tao Zhang; Changbao Chen (Rhizosphere, 2025)

Fossil wood of Pinus from the Pliocene of western Yunnan, China and its palaeoclimatic implications - Zhi-Hui Song; Zhuo-Er Wang; Rui Cao; Zhao-Shuai Wang; Huai Wang; Gui-Hua Chen; Jing-Yu Wu (Review of Palaeobotany and Palynology, 2025)

Soil organic carbon dynamics (2008–2020) across different cultivated land use types in a subtropical region - Jianming Li; Siqi Li; Rui Zhao; Shihe Xing; Hanyue Chen; Yan Huang; Liming Zhang; Jing Li (Geoderma Regional, 2025)

Enhancing the co-utilization of methanol and CO2 into 1-butanol by equipping synergistic reductive glycine pathway in Butyribacterium methylotrophicum - Jing Wang; Shengji Li; Chenxi Ma; Rui Zhang; Jialun Qin; Kequan Chen; Xin Wang (Bioresource Technology, 2025)

Seismic Prediction Methods for Tidal Flat Sand Bodies in the Shunbei Area of the Tarim Basin - Zhi-peng Sun; Rui-zhao Yang; Jing-rui Chen; Hao Zhang; Shi-jie Zhang; Peng-hui Yang; Feng Geng (Applied Geophysics, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Efficient photothermal conversion and Z-scheme charge transfer in narrow-gap semiconductor heterojunction for photothermal-assisted photocatalysis - Yu-Ting Chen; Wen-Xi Xia; Yuan Zhou; Qi-Rui Zhang; Xiang-Bai Chen; Liang Ma; Si-Jing Ding (Journal of Environmental Chemical Engineering, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Transcriptome Analysis Reveals the lncRNA-mRNA Co-expression Network Regulating the Aestivation of Sea Cucumber - Xiaomei Chen; Wentao Han; Rui Yang; Xuan Zhu; Shengwen Li; Yangfan Wang; Xue Sun; Yuli Li; Lisui Bao; Lingling Zhang; Shi Wang; Jing Wang (Marine Biotechnology, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Assessing the distribution pattern of Saussurea medusa under climate change using an optimized MaxEnt model in Qinghai-Xizang Plateau - Jing-Hua Chen; Rui-Tao Yu (Environmental Monitoring and Assessment, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Advances in thermochemical valorization of biomass towards carbon neutrality - Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Resources, Conservation and Recycling, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

Flowering delay in apple could alleviate frost-induced yield loss under climate change in China - Renwei Chen; Jing Wang; Bin Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenjiang Qu; Lu Liu (Agricultural and Forest Meteorology, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Are air travelers willing to pay for mandatory carbon emission policies? Evidence from China - Bao-Jun Tang; Rui Yan; Jun-Yu Chen; Chang-Jing Ji (Sustainable Production and Consumption, 2024)

Late Neogene monsoonal climate in the southeastern margin of the Tibetan Plateau revealed by leaf physiognomy evidence - Zhuo-Er Wang; Gui-Hua Chen; Rui Cao; Zhi-Hui Song; Zhao-Shuai Wang; Huai Wang; Su-Ting Ding; Jing-Yu Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Contribution of alkaline magmas to the petrogenesis of Triassic aluminous A-type granites on Liaodong Peninsula, Northeastern China - Yu-Sheng Zhu; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Lei Xu; Rui Li; Bao-Quan Zhou (Lithos, 2024)

The source and dissemination of ARGs in pristine environments: Elucidating the role of migratory birds in the Arctic - Qin Shu; Hui Gao; Rui-jing Li; Hai-yang Chen; Guang-shui Na (Journal of Hazardous Materials, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Comparison of prenatal and postnatal exposure to neonicotinoids and their temporal trends in breast milk - Kaiqin Huang; Meiqing Lin; Jing Yi; Guocheng Liu; Rui Hua; Yangyang Liu; Yanji Qu; Cairong Chen; Shengtao Ma (Science of The Total Environment, 2024)

Alternations in the element stoichiometry of the grasses drive the aboveground C:N:P ratio of an agriculturally improved pasture on karst in response to differential N and P fertilization - Jin Ye; Jing Zhou; Fugui Yang; Zhou Li; Rui Dong; David Horne; Ignacio Lopez; Zhibo Zhou; Jihui Chen (Plant and Soil, 2024)

End-to-end stereo matching network with two-stage partition filtering for full-resolution depth estimation and precise localization of kiwifruit for robotic harvesting - Xudong Jing; Hanhui Jiang; Shiao Niu; Haosen Zhang; Bryan Gilbert Murengami; Zhenchao Wu; Rui Li; Chengquan Zhou; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Deciphering pathogens inactivation mechanism during anaerobic co-digestion of food waste and waste activated sludge: The role of pH - Rui Tang; Qi Zhang; Yong-Dong Chen; Wen-Jing Bai; Jiao-Jiao Xu; Yilin Pang; Ying An; Zhen Zhou; Zhen-Hu Hu (Chemical Engineering Journal, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

A nationwide characterization of organochlorine pesticides (OCPs) in livestock and poultry food products across China: Residual levels, origin and the associated health risks - Lu Chen; Yongzhong Qian; Xu Wang; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Chemosphere, 2024)

Mechanical and hydraulic characteristics of unvegetated or vegetated loess soils amended with xanthan gum - Jing Ni; Rui-Jie Zhao; Jia-Qi Chen; Xue-Yu Geng (Transportation Geotechnics, 2024)

The premixed flame structure and combustion mechanism of clean hydrogen mixed with multi-component natural gas - Sheng Qi; Yuntao Li; Shuo Zhou; Qi Jing; Laibin Zhang; Rui Zhou; Wanyun Chen; Tong Li (Fuel, 2024)

Environmental pollution of paraben needs attention: A study of methylparaben and butylparaben co-exposure trigger neurobehavioral toxicity in zebrafish - Jing Xiang; Bing-Rui Lv; Ya-jun Shi; Wen-ming Chen; Ji-liang Zhang (Environmental Pollution, 2024)

Higher risk of spring frost under future climate change across China's apple planting regions - Renwei Chen; Jing Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenzhen Zhang; Lingxuan Zhao; Zhenjiang Qu; Lu Liu (European Journal of Agronomy, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Effect of chitooligosaccharides in inhibiting textural deterioration of chicken myofibril protein gel induced by high temperature - Yuntao Wang; Jing Chen; Rui Li; Shasha Wang; Ke Li; Yu Wang; Si Qiu; Dianbo Zhao; Yanhong Bai (Food Hydrocolloids, 2024)

Covalent organic framework with bioinspired N,S-anchored single atom sites for photocatalytic CO2 reduction reaction - Zi-Xian Pan; Shuai Yang; Xi Chen; Jing-Xian Luo; Rui-Zhi Zhang; Peng Yang; Qing Xu; Jie-Yu Yue (Chemical Engineering Journal, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

A reinforcement learning-driven adaptive decomposition algorithm for multi-objective hybrid seru system scheduling considering worker transfer - Yuting Wu; Ling Wang; Rui Li; Jing-fang Chen (Swarm and Evolutionary Computation, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Short- and long-term prediction models of rubber tree powdery mildew disease index based on meteorological variables and climate system indices - Rui Bai; Jing Wang; Ning Li; Renwei Chen (Agricultural and Forest Meteorology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Effects of cations on biofilms in gravity-driven membrane system: Filtration performance and mechanism investigation - Rui Chen; Daliang Xu; Jing Zhao; Xiaobin Tang; Haiyang Yang; Heng Liang (Water Research, 2024)

Revolutionizing sustainable economic growth in China: Harnessing natural resources, green development, and fintech for a greener future. - Liang Chen; Rui Ma; Jing Li; Fengjiao Zhou (Resources Policy, 2024)

Fe-Zn bimetallic oxide functionalized biochar for enhanced adsorption of enrofloxacin in water - Guodong Hong; Rui Shan; Jing Gu; Taoli Huhe; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

Catalytic reforming of polypropylene to produce hydrogen: Influence of support characteristics and active metal type in catalyst - Shuxiao Wang; Yibo Sun; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Fuel, 2024)

Risk factors, outcomes, and epidemiological and etiological study of hospitalized COVID-19 patients with bacterial co-infection and secondary infections - Yishan Duan; Jing Wang; Suyan Wang; Rui Zhang; Jinrui Hu; Weimin Li; Bojiang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background As a common complication of viral respiratory tract infection, bacterial infection was associated with higher mortality and morbidity. Determining the prevalence, culprit pathogens, outcomes, and risk factors of co-infection and secondary infection occurring in hospitalized patients with coronavirus disease 2019 (COVID-19) will be beneficial for better antibiotic management. Methods In this retrospective cohort research, we assessed clinical characteristics, laboratory parameters, microbiologic results, and outcomes of laboratory-confirmed COVID-19 patients with bacterial co-infection and secondary infection in West China Hospital from 2022 December 2nd to 2023 March 15th. Results The incidence of bacterial co-infection and secondary infection, as defined by positive culture results of clinical specimens, was 16.3% (178/1091) and 10.1% (110/1091) respectively among 1091 patients. Acinetobacter , Klebsiella , and Pseudomonas were the most commonly identified bacteria in respiratory tract samples of COVID-19 patients. In-hospital mortality of COVID-19 patients with co-infection (17.4% vs 9.5%, p = 0.003) and secondary infection (28.2% vs 9.5%, p < 0.001) greatly exceeded that of COVID-19 patients without bacterial infection. Cardiovascular disease (1.847 (1.202–2.837), p = 0.005), severe COVID-19 (1.694 (1.033–2.778), p = 0.037), and critical COVID-19 (2.220 (1.196–4.121), p = 0.012) were proved to be risk factors for bacterial co-infection, while only critical COVID-19 (1.847 (1.202–2.837), p = 0.005) was closely related to secondary infection. Conclusions Bacterial co-infection and secondary infection could aggravate the disease severity and worsen clinical outcomes of COVID-19 patients. Notably, only critical COVID-19 subtype was proved to be an independent risk factor for both co-infection and secondary infection. Therefore, standard empirical antibiotics was recommended for critically ill COVID-19 rather than all the inpatients according to our research.

The residues and health risk assessment of polychlorinated biphenyls (PCBs) in Pheretima (an earthworm-derived traditional medicine) from southeastern China - Yun-Jing Zhang; Jing Sun; Xiao-Jiang Chen; Rui Cheng; Zhi-Tong Liu; Ling Cao; You-Long Feng (Environmental Science and Pollution Research, 2024)

Individual ambient ozone exposure during pregnancy and adverse birth outcomes: Exploration of the potentially vulnerable windows - Chenqing Zhang; Jie Yang; Jing Wei; Yuansheng Liu; Huiping Zhu; Xiaobo Li; Jiajia Wang; Rui Chen (Journal of Hazardous Materials, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Speciation analysis and toxicity evaluation of arsenolipids—an overview focusing on sea food - Caiyan Li; Jing Chen; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Sai-Yi Zhong (Archives of Toxicology, 2024)

L.acidophilus participates in intestinal inflammation induced by PM2.5 through affecting the Treg/Th17 balance - Jie Xu; Jing Wang; Yuefeng He; Rui Chen; Qingtao Meng (Environmental Pollution, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Neuroprotective α-pyrones from Nigrospora oryzae, an endophytic fungus residing in Taxus chinensis var. mairei - Zi Yun Fan; Jing Peng; Jun Qiao Lou; Yong Chen; Xue Ming Wu; Rui Tan; Ren Xiang Tan (Phytochemistry, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Does digital economy curb carbon intensity? New insights from China - Rui Yang; Bing Chen; Jing Wu (Environmental Science and Pollution Research, 2023)

Co-pyrolysis of textile dyeing sludge/litchi shell and CaO: Immobilization of heavy metals and the analysis of the mechanism - Danni Li; Rui Shan; Jing Gu; Yuyuan Zhang; Xianhai Zeng; Lu Lin; Haoran Yuan; Yong Chen (Waste Management, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Mechanistic insight into the hydrogen transfer pathway for selective upcycling of PET to arenes - Huiyu Liu; Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2023)

A novel method based on deep learning model for national-scale landslide hazard assessment - Rui Yuan; Jing Chen (Landslides, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Effects of microplastics on functional genes related to CH4 and N2O metabolism in bacteriophages during manure composting and its planting applications - Wei-Kang Deng; Jun-Liang He; Jing-Yuan Chen; Rui-Ting Wu; Si-Cheng Xing; Xin-Di Liao (Journal of Hazardous Materials, 2023)

Rapid imaging approach for marine controlled-source electromagnetic with deployed transmission system - Rui Yang; Xuben Wang; Meng Wang; Xianhu Luo; Ming Deng; Jianen Jing; Kai Chen (Journal of Applied Geophysics, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Elevation, bedrock exposure, land use, interbedded limestone and clastic rock, and vegetation coverage dominate the spatiotemporal variability of soil erosion in karst basin - Mei Chen; Jia-yong Gao; Hong-lian Chen; Jun Jing; Rui Li (Journal of Mountain Science, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

The interference between effects of PFAS exposure on thyroid hormone disorders and cholesterol levels: an NHANES analysis - Liang Zheng; Zhecun Wang; Rui Yang; Wanna Chen; Jing Zhang; Ruixia Li; Weiming Lv; Bo Lin; Jiajun Luo (Environmental Science and Pollution Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Control of chemical and microbial pollutants in liquid-solid phases of sewer pipes by Fe(II)-activated persulfate: Performance and mechanism of simultaneous removal - Jinsuo Lu; Hang Zhao; Zhiqiang Zhang; Feng Jin; Heliang Pang; Jing Yang; Xuan Wang; Rui Chen (Chemical Engineering Journal, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

The tectono-magmatic formation and submarine geohazards of the Japan Sea: Constraints from in-situ trace elements and Sr isotopes of plagioclase and clinopyroxene - Shuang-Shuang Chen; Jing Chen; Qiuming Cheng; Rui Gao; Jia-Qi Liu (Marine and Petroleum Geology, 2023)

Bio-inspired functionalization of electrospun nanofibers with anti-biofouling property for efficient uranium extraction from seawater - Dingyang Chen; Xinyue Zhao; Xiaofei Jing; Rui Zhao; Guangshan Zhu; Ce Wang (Chemical Engineering Journal, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Moderation device design for detecting hidden highly enriched uranium based on D-T neutron generator - Shang-Rui Jiang; Guang-Yu Shi; Si-Yuan Chen; Shi-Wei Jing; Chao Liu (Annals of Nuclear Energy, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Changes of Iodine Nutritional Status in the Elderly after Replacing Iodized Salt with Non-Iodized Salt for Half a Year - Min Li; Rui Wang; Jiaxi Lu; Weidong Li; Yichun Hu; Jing Chen; Wei Ma; Lichen Yang (Biological Trace Element Research, 2023)

A national-scale distribution of organochlorine pesticides (OCPs) in cropland soils and major types of food crops in China: Co-occurrence and associated risks - Lu Chen; YongZhong Qian; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Science of The Total Environment, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

The off-axis plume–ridge interaction model: Confirmation from the mineral chemistry of Cretaceous basalts of the Ontong Java Plateau - Jing Chen; Shuang-Shuang Chen; Donald B. Dingwell; Rui Gao; Jia-Qi Liu (Chemical Geology, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

Flavor components detection and discrimination of isomers in Huaguo tea using headspace-gas chromatography-ion mobility spectrometry and multivariate statistical analysis - Wenhui Lu; Jing Chen; Xuebo Li; Yinghua Qi; Rui Jiang (Analytica Chimica Acta, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

A review on the NOx precursors release during biomass pyrolysis - Hongyuan Chen; Rui Shan; Fengxiao Zhao; Jing Gu; Yuyuan Zhang; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2023)

A hybrid deep learning method for landslide susceptibility analysis with the application of InSAR data - Rui Yuan; Jing Chen (Natural Hazards, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

Nutrient Reabsorption Mechanism Adapted to Low Phosphorus in Wild and Cultivated Soybean Varieties - Wenyue Shen; Rui Guo; Yaxuan Zhao; Danping Liu; Jing Chen; Ningning Miao; Shujuan Gao; Tao Zhang; Lianxuan Shi (Journal of Plant Growth Regulation, 2022)

Alterations in gut microbiota affect behavioral and inflammatory responses to methamphetamine in mice - Simin Lai; Jing Wang; Biao Wang; Rui Wang; Guodong Li; Yuwei Jia; Teng Chen; Yanjiong Chen (Psychopharmacology, 2022)

LncRNA SNHG14 is beneficial to oxygen glucose deprivation/reoxygenation-induced neuro-2a cell injury via mir-98-5p sequestration-caused BCL2L13 upregulation - Gaolian Zhang; Jianhui Guo; Jing Zeng; Xiaoning Zhang; Rui Chen; Gang Wang; Weibin Liang (Metabolic Brain Disease, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Development of sustainable self-compacting concrete using recycled concrete aggregate and fly ash, slag, silica fume - Zhanggen Guo; Jing Zhang; Tao Jiang; Tianxun Jiang; Chen Chen; Rui Bo; Yan Sun (European Journal of Environmental and Civil Engineering, 2022)

Complete genome sequence of a novel mitovirus from the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Chengjun Li; Rui Qiu; Xiaojie Li; Jun Zhao; Jingke Bai; Yuguo Chen; Shujun Li (Archives of Virology, 2021)

Oceaniglobus trochenteri sp. nov., isolated from the gut microflora of top shell (Trochus maculatus Linnaeus) - Zhuo Chen; Shuai-Ting Yun; Ming-Jing Zhang; Rui Yin; Yan-Xia Zhou (Archives of Microbiology, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Phase field model for hydraulic fracture propagation in porous medium and numerical simulation analysis of hydraulic fracture propagation in a layered reservoir - Liang-Ping Yi; Chang-Xin Yang; Rui Chen; Jing-Yi Zhu; Xiao-Hua Zhu; Zhao-Zhong Yang; Xiao-Gang Li (Arabian Journal of Geosciences, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Candidate proteins involved in the calyx abscission process of ‘Kuerlexiangli’ (Pyrus sinkiangensis Yu) identified by iTRAQ analysis - Xin Gong; Jianping Bao; Jing Chen; Kaijie Qi; Zhihua Xie; Weikang Rui; Guowei Hao; Katsuhiro Shiratake; Shahrokh Khanizadeh; Shaoling Zhang; Shutian Tao (Acta Physiologiae Plantarum, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

The relief effects of organic acids on Scirpus triqueter L. under pyrene–lead stress - Xinying Zhang; Jing Chen; Xiaoyan Liu; Xueping Chen; Lu Liu; Yinghu Niu; Rui Wang (Environmental Science and Pollution Research, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

A new phenanthrene and a new 9,10-dihydrophenanthren from Bulbophyllum retusiusculum - Jing Sun; Yan Zhang; Lijun Chen; Rui Zhan; Yegao Chen (Natural Product Research, 2018)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Comparison of chemical compositions in air particulate matter during summer and winter in Beijing, China - Rui Chen; Jing Cheng; Jungang Lv; Lijun Wu; Jing Wu (Environmental Geochemistry and Health, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Biological traits yield divergent phylogeographical patterns between two aphids living on the same host plants - Fang Fang; Jing Chen; Li‐Yun Jiang; Rui Chen; Ge‐Xia Qiao (Journal of Biogeography, 2017)
Aim Animals' phylogeographical patterns are frequently explained by Pleistocene glacial fluctuations and topographical environments. However, species‐specific biological traits are thought to have profound impacts on distribution patterns, particularly in aphids. We hypothesize that the phylogeographical patterns and/or population dynamics of two sympatric aphids may be different due to their different reproductive modes and feeding sites, even though they share the same hosts and environmental conditions. Location China. Methods We explored our hypothesis in Chaitophorus saliniger and Tuberolachnus salignus , two aphids that share the same host plants (genus Salix ) but differ biologically. Chaitophorus saliniger is characterized by alternating sexual and asexual reproduction and only feeds on willow leaves, whereas T. salignus has obligate asexual reproduction and feeds on trunks and branches. The genetic diversity, population structure and demographic history of the aphids were analysed based on both mitochondrial DNA (cytochrome c oxidase subunit I and cytochrome b ) and nuclear DNA (translation elongation factor 1 alpha). Ecological niche models ( ENM s) were used to explore historical changes in distribution. The chief environmental variables that discriminate the different haplogroups were identified through multivariate statistical analysis. Results There were striking differences in the phylogeographical patterns between the species. The sexual C. saliniger exhibited higher genetic diversity and population variations than the asexual T. salignus . According to genetic analyses and ENM s, both species experienced glacial contraction and post‐glacial expansion. Multivariate statistical analysis revealed that the climatic differences between the divergent haplogroups were explained by principal components mainly loaded with temperature and elevation. Main conclusions Our results suggest that species‐specific biological traits and historical climate fluctuations have both shaped the current phylogeographical patterns of both aphid species. Their distinct genetic diversity and population structures highlight the importance of intrinsic biological features in driving phylogeographical patterns.

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Application of Biotic Ligand Model in Predicting Copper Acute Toxicity to Carp (Cyprinidae) - Wanbin Wang; Qibin Liang; Jing Zhao; Rui Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

A new thalloid liverwort: Pallaviciniites sandaolingensis sp. nov. from the Middle Jurassic of Turpan–Hami Basin, NW China - Rui-Yun Li; Xue-lian Wang; Jing-Wei Chen; Sheng-Hui Deng; Zi-Xi Wang; Jun-Ling Dong; Bai-Nian Sun (PalZ, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Over-expression of StLCYb increases β-carotene accumulation in potato tubers - Xiao-yan Song; Wen-jiao Zhu; Rui-min Tang; Jing-hui Cai; Min Chen; Qing Yang (Plant Biotechnology Reports, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

The seasonal variations in the significant wave height and sea surface wind speed of the China’s seas - Chongwei Zheng; Jing Pan; Yanke Tan; Zhansheng Gao; Zhenfeng Rui; Chaohui Chen (Acta Oceanologica Sinica, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

3-D observations of a red tide event in the offshore water along the western Guangdong coast - Lingling Xie; Qingxiang Chen; Jianyu Hu; Shuwen Zhang; Xiaofei Yi; Fajin Chen; Rui Deng; Xiaodong Deng; Jing Wang; Yiquan Qi (Acta Oceanologica Sinica, 2015)

Isolation of α-glucosidase inhibitors including a new flavonol glycoside from Dendrobium devonianum - Jing Sun; Fudong Zhang; Miao Yang; Junjie Zhang; Lijun Chen; Rui Zhan; Ling Li; Yegao Chen (Natural Product Research, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

A miR-570 binding site polymorphism in the B7-H1 gene is associated with the risk of gastric adenocarcinoma - Weipeng Wang; Fang Li; Yong Mao; Huan Zhou; Jing Sun; Rui Li; Cuiping Liu; Weichang Chen; Dong Hua; Xueguang Zhang (Human Genetics, 2013)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Foot-and-mouth disease virus leader proteinase inhibits dsRNA-induced RANTES transcription in PK-15 cells - Dang Wang; Liurong Fang; Jing Bi; Quangang Chen; Lu Cao; Rui Luo; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)